The role of mobile money adoption in moderating the influence of access to finance in firm performance - Sam Z. Njinyah; Simplice Asongu; Sally Jones (African Governance and Development Institute (AGDI), 2022)
Africa is becoming the fastest-growing continent despite significant challenges to accessing finance and the use of technology. This research aims to examine the direct effect of mobile money adoption on firm performance and its indirect effect by examining how it moderates the effect of access to finance on firm performance. Quantitative data were obtained from the World Bank Enterprise Survey for Cameroon, Ivory Coast and Zimbabwe. A series of hierarchical regression analyses were done to test the hypotheses. The main findings show a negative significant relationship between mobile money adoption and firm performance while access to finance had a positive relationship. The moderation effect though positive was not significant. Research examining the effect of mobile money adoption in Africa on firm performance is limited and existing studies have focused on the determinants of mobile money usage.
Keywords: 330; Mobile money; Access to Finance; Firm Performance; Resource-based view; Sub Saharan Africa